Impairment of theta oscillations in the hippocampal CA1 region may mediate age-dependent movement alternations in the 5xFAD mouse model of Alzheimer’s disease - Hong Ni; Zhongzhao Guo; Jie Wang; Zilu Zhu; Chenyi Xia; Ming Xu; Guohui Zhang; Deheng Wang (Scientific Reports)
Abstract Clinical evidences indicate that multifaceted gait abnormalities may manifest in Alzheimer’s disease (AD) patients, which are associated with cognitive decline. Although the correlation between hippocampal theta power and locomotion has been known for a long time, the mechanisms by how hippocampal impairment participates in the altered gait seen in AD is not fully understood. To explore the manifestations of gait disorders in AD, we characterized gait performance in 3-, 6-, and 9-month-old male 5xFAD and control mice in the semi-automated, highly sensitive, Catwalk XT system. The 5xFAD mice displayed a decrease in kinetic parameters (average speed and cadence), and spatial parameters (paw area), while the temporal parameters (stance and swing time) were significantly increased. The parameters of interlimb coordination also displayed deficits. The majority of impairment variables related to the slow speed in 5xFAD mice at 9-month-old. We further explored the theta oscillations in the brain by in vivo tetrode recording of the hippocampal CA1. The results showed that the theta oscillations reduced in the hippocampal CA1 of 5xFAD mice, which related to the gait impairments. In conclusion, gait impairments started at 6 months of age, manifested at 9 months of age in 5xFAD mice. A reduction in theta oscillation power of the hippocampal CA1 may be responsible for the gait impairments.